Marketing mistakes and successes - Hartley, Robert F. 1927-; Claycomb, Cindy (Hoboken, New Jersey : Wiley, 2014)
"Marketing professionals have relied on Hartley's book for 30 years to uncover the best and worst marketing programs. Invitation to Research suggestions allow readers to take the case a step further, to investigate what has happened since the case was written, both to the company and even to some of the individuals involved. Learning Insights help marketing professionals see how certain practices--both errors and successes--cross company lines and are prone to be either traps for the unwary or success models. Each chapter has been updated to reflect the latest information available about each case"--
Includes bibliographical references and index.
Keywords: Marketing -- United States -- Case studies; BUSINESS & ECONOMICS / Marketing / General